Simple synthesis method of cobalt-based bimetallic oxide with large specific surface area

By controlling parameters such as solvent volume ratio and calcining temperature, the solubilized bimetallic oxide was synthesized by solvothermal method, which solved the problem of difficult preparation of large specific surface area materials in the prior art, and achieved the preparation of porous structures and large specific surface area materials. It has the advantages of simple process, low cost and environmental protection.

CN119390134APending Publication Date: 2025-02-07ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411659825.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

It is difficult to prepare cobalt-based bimetallic oxide materials with large specific surface areas, and their pore size distribution is relatively limited.

Method used

By controlling the solvent volume ratio and the calcining temperature of the precursor, the solubilized bimetallic oxide is synthesized by solvothermal method, including steps such as configuring a mixed solvent of glycerol and isopropanol, adding metal salts and stirring until completely dissolved, and performing water The steps of thermal reaction, washing and calcining are obtained by obtaining cobalt-based bimetallic oxide micro-nanomaterials with a porous structure and a large specific surface area.

Benefits of technology

The cobalt-based bimetal oxide micro-nano materials with different chemical compositions, morphology, specific surface area and pore size distribution are selected. The product has a porous structure and a large specific surface area, and the preparation process is simple, low cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390134A_ABST
    Figure CN119390134A_ABST
Patent Text Reader

Abstract

The invention discloses a simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area. The simple synthesis method comprises the following steps: (1) preparing a mixed solvent of glycerol and isopropanol; (2) weighing cobalt salt and another metal salt, adding the prepared mixed solvent, and stirring for dissolving; (3) adding deionized water and stirring; (4) transferring into a reaction kettle, sealing and reacting for 8-24 hours at 190 DEG C; (5) collecting a precursor product, washing and dispersing the precursor product into deionized water, and standing for 12-36 hours; (6) transferring into the reaction kettle again, sealing and reacting at 190 DEG C for 8-24 hours; (7) washing with absolute ethyl alcohol, and drying to obtain precursor powder; and (8) transferring the obtained powder product into a tubular furnace, and calcining in the air at 300-550 DEG C for 2-6 hours at the heating rate of 2-6 DEG C * min < 1 > to obtain the cobalt-based bimetallic oxide micro-nano material with the porous structure and the large specific surface area. The method is reasonable in design and has good practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of transition metal oxides, in particular to a simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area. Background Art

[0002] Cobalt-based bimetallic oxide materials are cheap, environmentally friendly, have multiple valence states and rich structures, and are a type of oxide with important industrial uses. Among these oxides, manganese cobalt oxide, zinc cobalt oxide, copper cobalt oxide, magnesium cobalt oxide, and iron cobalt oxide have shown many special physical and chemical properties in the fields of catalysis and electrochemical energy storage. In addition, its specific surface area, pore size distribution, and complex and varied morphological structure are one of the important factors affecting its physical and chemical properties. Therefore, the preparation of cobalt-based bimetallic oxides with large specific surface area and novel structure, and the study of their controllable morphology and size, is one of the research hotspots at this stage.

[0003] According to the existing literature, cobalt-based bimetallic oxide micro-nano materials can be prepared by template method, electrodeposition method, electrospinning method, and hydrothermal / solvothermal method. Among them, hydrothermal and solvothermal methods have become the most commonly used methods for preparing cobalt-based bimetallic oxide micro-nano materials due to their advantages of simple operation, low cost, low energy consumption, and controllable product particle size. There are literature reports that cobalt-based bimetallic oxide nanoflowers, nanosheets, nanorods, nanowires and other morphologies have been synthesized by hydrothermal or solvothermal methods. However, the cobalt-based bimetallic oxides prepared by hydrothermal or solvothermal methods reported in the literature have limited specific surface area and pore size distribution, making it difficult to prepare such materials with large specific surface area. Summary of the invention

[0004] The purpose of the present invention is to provide a simple synthesis method of cobalt-based bimetallic oxide micro-nano materials with a porous structure and a large specific surface area, comprising five transition metal oxide materials, namely, five cobalt-based bimetallic oxide micro-nano materials (manganese cobalt oxide, zinc cobalt oxide, copper cobalt oxide, magnesium cobalt oxide, iron cobalt oxide) with a porous structure and a large specific surface area. By simply controlling parameters such as the solvent volume ratio and the calcination temperature of the precursor, the cobalt-based bimetallic oxide micro-nano materials with different chemical compositions, different morphologies, different specific surface areas, and different pore size distributions can be selectively synthesized.

[0005] The present invention is achieved through the following technical solutions: A simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area comprises the following steps: (1) Preparing a mixed solvent of glycerol and isopropanol; (2) Weighing cobalt salt and another metal salt, adding them to the mixed solvent prepared in step (1), and stirring them thoroughly until they are completely dissolved; (3) adding deionized water to the solution in step (2) and stirring; (4) Transfer the solution obtained in step (3) into a reaction kettle, seal it, and react at 190° C. for 8 to 24 hours; (5) After the reaction is completed, the precursor product is collected by centrifugation, washed, dispersed in deionized water, and allowed to stand for 12 to 36 hours; (6) Transfer the deionized water solution containing the precursor in step (5) to the reaction kettle again, seal it, and react at 190° C. for 8 to 24 hours; (7) After the reaction is completed, washing with anhydrous ethanol and drying to obtain a precursor powder; (8) The powder product obtained in step (7) is transferred to a tube furnace and calcined in air at 300-550°C for 2-6 hours at a heating rate of 2-6°C min. −1 , a cobalt-based bimetallic oxide micro-nano material with a porous structure and a large specific surface area can be obtained.

[0006] More preferably, in step (1), the volume of the mixed solvent is 36-40 mL.

[0007] Further preferably, in step (1), the volume ratio (v:v) of glycerol to isopropanol is 1:(1-7).

[0008] Further preferably, in step (2), the other metal salt is a zinc salt, a manganese salt, a copper salt, a magnesium salt or an iron salt. The salt raw material used is a nitrate or a chloride.

[0009] Further preferably, the salt raw materials of the cobalt salt and the other metal salt are nitrates, and the molar ratio of the cobalt salt to the other metal salt is 2:1.

[0010] Further preferably, in step (3), 1 to 5 mL of deionized water is added, and the total volume of glycerol, isopropanol and deionized water is ensured to be 41 mL.

[0011] After the initial solvent thermal reaction of the method of the present invention is completed, the obtained precursor product can be transformed into the corresponding layered double metal hydroxide after aging in deionized water; this transformation process can be more thorough in the subsequent hydrothermal stage. The anions of the nitrate or chloride used in the synthesis stage can regulate the interlayer spacing. The calcination temperature and heating rate used in the calcination stage can directly determine the specific surface area, pore size distribution, chemical composition, etc. of the final material.

[0012] Compared with the prior art, the present invention has the following advantages: (1) By simply controlling the reaction parameters, cobalt-based bimetallic oxide micro-nanomaterials with different chemical compositions, different morphologies, different specific surface areas, and different pore size distributions can be obtained; (2) The required equipment is simple, the preparation process is simple, and the cost is low; (3) The product preparation process is easy to control and has good reproducibility; (4) No toxic substances are produced during the preparation process, and there is no pollution to the environment.

[0013] The invention has reasonable design and good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0016] Figure 1 The porous structure and large specific surface area ZnCo prepared in Example 1 of the present invention 2 O 4 Scanning electron microscope (SEM) image of micron flower.

[0017] Figure 2 The porous structure and large specific surface area MnCo prepared in Example 2 of the present invention 2 O 4.5 Scanning electron microscope (SEM) image of nanosheets.

[0018] Figure 3 The porous structure and large specific surface area MgCo prepared in Example 3 of the present invention are shown. 2 O 4 Scanning electron microscope (SEM) images of microspheres. DETAILED DESCRIPTION

[0019] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0021] The specific embodiments of the present invention are described in detail below with reference to the accompanying drawings. Example 1

[0022] A ZnCo with porous structure and large specific surface area 2 O 4 The preparation method of micron flower comprises the following steps: (1) Take 20 mL of glycerol and 20 mL of isopropanol, prepare a mixed solvent, and stir thoroughly. Ultrasonic waves can be used to assist in the stirring and dissolution of the metal salt.

[0023] (2) Weigh 1 mmol of Zn(NO 3 ) 2 6H 2 O and 2 mmol Co(NO 3 ) 2 6H 2 O is added to the mixed solvent of step (1) and stirred until it is completely dissolved and a uniform solution is formed.

[0024] (3) Add 1 mL of deionized water to the solution in step (2) and stir to mix.

[0025] (4) The solution in step (3) was transferred to a 50 mL polytetrafluoroethylene-lined autoclave and placed in an oven at 190°C for 12 h.

[0026] (5) After the reactor was cooled naturally to room temperature, the reaction precipitate was collected and washed three times with anhydrous ethanol and deionized water.

[0027] (6) Ultrasonic disperse the precipitate in 40 mL of deionized water and let it stand for 24 h.

[0028] (7) The precipitate was collected by centrifugation and washed three times with anhydrous ethanol. The precipitate was dried in a drying oven at 60 °C to obtain a precursor powder.

[0029] (8) The precursor powder was calcined in a muffle furnace at 350 °C for 3 h at a heating rate of 5 °C min −1 , and finally obtain ZnCo 2 O 4 Micron flower.

[0030] like Figure 1 As shown, the porous ZnCo 2 O4 Scanning photo of micron flower, its specific surface area is 125.14m 2 ·g −1 The average pore size is 13.35nm, mainly concentrated at 6.06nm. Example 2

[0031] A MnCo with porous structure and large specific surface area 2 O 4.5 The method for preparing the nanosheet comprises the following steps: (1) Take 5 mL of glycerol and 35 mL of isopropanol, prepare a mixed solvent, and stir thoroughly. Ultrasonic waves can be used to assist in the stirring and dissolution of the metal salt.

[0032] (2) Weigh 1 mmol of Mn(NO 3 ) 2 ·4H 2 O and 2 mmol Co(NO 3 ) 2 6H 2 O is added to the mixed solvent in step (1) and stirred until it is completely dissolved and a uniform solution is formed.

[0033] (3) Add 1 mL of deionized water to the solution in step (2) and stir to mix.

[0034] (4) The solution in step (3) was transferred to a 50 mL polytetrafluoroethylene-lined autoclave and placed in an oven at 190°C for 12 h.

[0035] (5) After the reactor was cooled naturally to room temperature, the reaction precipitate was collected and washed three times with anhydrous ethanol and deionized water.

[0036] (6) Ultrasonic disperse the precipitate in 40 mL of deionized water and let it stand for 24 h.

[0037] (7) Transfer the 40 mL of deionized water solution containing the precursor in step (6) into the 50 mL reactor again, seal it, and react at 190 °C for 12 h.

[0038] (8) The powder product obtained in step (7) was transferred to a tube furnace and calcined in air at 350 °C for 3 h at a heating rate of 2 °C min. −1 , you can get MnCo with a porous structure and a large specific surface area 2 O 4.5 Nanosheets.

[0039] like Figure 2 The porous MnCo 2 O 4.5Scanning photo of nanosheets, with a specific surface area of ​​104.93m 2 ·g −1 , the average pore size is 14.15nm. Example 3

[0040] A MgCo with porous structure and large specific surface area 2 O 4 The method for preparing microspheres comprises the following steps: (1) Take 15 mL of glycerol and 25 mL of isopropanol, prepare a mixed solvent, and stir thoroughly. Ultrasonic waves can be used to assist in the stirring and dissolution of the metal salt.

[0041] (2) Weigh 1 mmol of Mg(NO 3 ) 2 6H 2 O and 2 mmol Co(NO 3 ) 2 6H 2 O is added to the mixed solvent of step (1) and stirred until it is completely dissolved and a uniform solution is formed.

[0042] (3) Add 1 mL of deionized water to the solution in step (2) and stir to mix.

[0043] (4) The solution in step (3) was transferred to a 50 mL polytetrafluoroethylene-lined autoclave and placed in an oven at 190°C for 12 h.

[0044] (5) After the reactor was cooled naturally to room temperature, the reaction precipitate was collected and washed three times with anhydrous ethanol and deionized water.

[0045] (6) Ultrasonic disperse the precipitate in 40 mL of deionized water and let it stand for 24 h.

[0046] (7) The precipitate was collected by centrifugation and washed three times with anhydrous ethanol. The precipitate was dried in a drying oven at 60 °C to obtain a precursor powder.

[0047] (8) The precursor powder was calcined in a muffle furnace at 400 °C for 3 h at a heating rate of 2 °C min. −1 , and finally MgCo 2 O 4 Microspheres.

[0048] like Figure 3 The porous MgCo 2 O 4 Microsphere scanning photo, the comparison area is 69.4m 2 ·g −1 , the average pore size is 21.2nm.

[0049] The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.

Claims

1. A simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area, characterized in that: The steps include: (1) Preparing a mixed solvent of glycerol and isopropanol; (2) Weighing cobalt salt and another metal salt, adding them to the mixed solvent prepared in step (1), and stirring them thoroughly until they are completely dissolved; (3) adding deionized water to the solution in step (2) and stirring; (4) Transfer the solution obtained in step (3) into a reaction kettle, seal it, and react at 190° C. for 8 to 24 hours; (5) After the reaction is completed, the precursor product is collected by centrifugation, washed, dispersed in deionized water, and allowed to stand for 12 to 36 hours; (6) Transfer the deionized water solution containing the precursor in step (5) to the reaction kettle again, seal it, and react at 190° C. for 8 to 24 hours; (7) After the reaction is completed, washing with anhydrous ethanol and drying to obtain a precursor powder; (8) The powder product obtained in step (7) is transferred to a tube furnace and calcined in air at 300-550°C for 2-6 hours at a heating rate of 2-6°C min. −1 , a cobalt-based bimetallic oxide micro-nano material with a porous structure and a large specific surface area can be obtained.

2. The simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area according to claim 1, characterized in that: In step (1), the volume of the mixed solvent is 36-40 mL.

3. The simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area according to claim 2, characterized in that: In step (1), the volume ratio of glycerol to isopropanol is 1:(1-7).

4. The simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area according to claim 1, characterized in that: In step (2), the other metal salt is a zinc salt, a manganese salt, a copper salt, a magnesium salt or an iron salt.

5. The simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area according to claim 2, characterized in that: In step (3), add 1 to 5 mL of deionized water, and ensure that the total volume of glycerol, isopropanol, and deionized water is 41 mL.

6. The simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area according to claim 4, characterized in that: The salt raw materials used are nitrates or chlorides.

7. The simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area according to claim 6, characterized in that: The salt raw materials of the cobalt salt and another metal salt are nitrates, and the molar ratio of the cobalt salt to the other metal salt is 2:

1.

8. The simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area according to claim 3, characterized in that: The volume ratio of glycerol to isopropanol is 1:

1.

9. The simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area according to claim 3, characterized in that: The volume ratio of glycerol to isopropanol is 1:

7.

10. The simple synthesis method of a cobalt-based bimetallic oxide with a large specific surface area according to claim 3, characterized in that: The volume ratio of glycerol to isopropanol is 3:5.